2019
DOI: 10.1002/hbm.24701
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a temporoparietal junction subtype of Alzheimer's disease

Abstract: Alzheimer's disease (AD) subtypes have been described according to genetics, neuropsychology, neuropathology, and neuroimaging. Thirty-one patients with clinically probable AD were selected based on perisylvian metabolic decrease on FDG-PET.They were compared to 25 patients with a typical pattern of decreased posterior metabolism. Tree-based machine learning was used on those 56 images to create a classifier that was subsequently applied to 207 Alzheimer's Disease Neuroimaging Initiative (ADNI) patients with A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…FDG-PET may indicate a decrease in cerebral glucose metabolism that occurs prior to the macroscopic atrophy detectable with MRI, rendering the technique potentially more sensitive to early neurodegenerative processes [ 8 10 ]. While previous hypothesis-driven studies have also reported differential hypometabolic FDG-PET patterns amongst AD dementia patients [ 11 13 ], to our knowledge, FDG-PET has not yet been used for identifying neurodegeneration subtypes of AD in a data-driven manner. Given that detection of an “AD-typical” hypometabolism pattern by visual inspection of individual patients’ FDG-PET scans is commonly used for differential dementia diagnosis in research and clinical settings [ 7 , 12 , 14 16 ], a systematic evaluation of whether and how specific AD neurodegeneration subtypes are reflected in FDG-PET data can have important diagnostic implications.…”
Section: Introductionmentioning
confidence: 97%
“…FDG-PET may indicate a decrease in cerebral glucose metabolism that occurs prior to the macroscopic atrophy detectable with MRI, rendering the technique potentially more sensitive to early neurodegenerative processes [ 8 10 ]. While previous hypothesis-driven studies have also reported differential hypometabolic FDG-PET patterns amongst AD dementia patients [ 11 13 ], to our knowledge, FDG-PET has not yet been used for identifying neurodegeneration subtypes of AD in a data-driven manner. Given that detection of an “AD-typical” hypometabolism pattern by visual inspection of individual patients’ FDG-PET scans is commonly used for differential dementia diagnosis in research and clinical settings [ 7 , 12 , 14 16 ], a systematic evaluation of whether and how specific AD neurodegeneration subtypes are reflected in FDG-PET data can have important diagnostic implications.…”
Section: Introductionmentioning
confidence: 97%
“…Interestingly, these cortical regions have an extended multi-decade duration of brain development, thus potentially being more vulnerable to negative effects, e.g., cocaine consumption, which begins in the first three decades (61). Another implication of these structural alterations, particularly in the temporoparietal junction, is their importance in neurodegenerative diseases (62,63). Further studies are needed to investigate the effects of CUD on aging and potential accelerated neurodegeneration.…”
Section: Discussionmentioning
confidence: 99%
“…While previous hypothesis-driven studies have also reported differential hypometabolic FDG-PET patterns among AD dementia patients (10,14,15), to our knowledge, FDG-PET has not yet been used for identifying neurodegeneration subtypes of AD in a data-driven manner.…”
Section: Introductionmentioning
confidence: 88%